ANALISIS TINGKAT PEMAHAMAN KARYAWAN BANK TERHADAP AKAD PEMBIAYAAN PRODUK KREDIT PEMILIKAN RUMAH (KPR) BANK SYARIAH MANDIRI KANTOR CABANG ACEH - Leni Oktaviani; Suazhari Suazhari (FEB Universitas Syiah Kuala, 2019)
This research was conducted to analyze the comprehension level of bank employees regarding financing agreement of morgage loans (KPR) products at Bank Syariah Mandiri Aceh Branch. This research is considered as a qualitative descriptive research, which is a research method aiming to describe information collected through the research. Populations and research samples are 5 (five) employees of Bank Syariah Mandiri in Aceh Branch Office from the financing agreement of house ownership product department, chosen using purposive sampling technique. The data used in this research are the primary and secondary data. Data collecting method is through the interview and documentation. The result indicates that employees’ comprehension level regarding financing agreement of housing ownership credit (KPR) product is considered very low. The explanation described by employees about financing agreement of KPR (murabahah agreement) is yet to be corresponding with appropriate sharia and fatwa DSN-MUI No: 4/DSN-MUI/2000 regarding Murabahah.Keywords: KPR, Murabahah, Comprehension, Fatwa DSN-MUI ABSTRAKPenelitian ini bertujuan untuk menganalisis tingkat pemahaman karyawan bank terhadap akad pembiayaan produk kredit pemilikan rumah (KPR) Bank Syariah Mandiri Kantor Cabang Aceh. Jenis penelitian ini adalah penelitian kualitatif deskriptif yaitu metode penelitian yang bertujuan mendeskripsikan informasi yang diperoleh dari hasil penelitian. Populasi dan sampel penelitian yaitu karyawan Bank Syariah Mandiri Kantor Cabang Aceh yang berjumlah 5 orang berasal dari karyawan pembiayaan produk KPR diambil melalui teknik purposive sampling. Data yang digunakan yaitu data primer dan skunder. Teknik pengumpulan data melalui wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa tingkat pemahaman karyawan bank terhadap akad pembiayaan produk kredit pemilikan rumah (KPR) masing sangat kurang. Penjelasan karyawan terhadap akad (KPR) ( akad murabahah) masih belum sesuai dengan syariah dan fatwa DSN-MUI No: 4/DSN-MUI/2000 tentang Murabahah.